2014
DOI: 10.1186/1471-2148-14-65
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to gene exchange in hybridizing field crickets: the role of male courtship effort and cuticular hydrocarbons

Abstract: BackgroundPre-zygotic barriers often involve some form of sexual selection, usually interpreted as female choice, as females are typically the choosier sex. However, males typically show some mate preferences, which are increasingly reported. Here we document previously uncharacterized male courtship behavior (effort and song) and cuticular hydrocarbon (CHC) profiles in the hybridizing crickets Gryllus firmus and G. pennsylvanicus. These two species exhibit multiple barriers to gene exchange that act throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 80 publications
2
27
0
Order By: Relevance
“…Hybrid zone cobaltinus males appear to differentiate heterospecific females from conspecific females based on their cuticular hydrocarbon profiles (Peterson et al., )—chemicals that insects commonly used to identify potential mates and that can contribute to premating barriers between species (e.g. Havens & Etges, ; Maroja et al., ; Rundle & Dyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid zone cobaltinus males appear to differentiate heterospecific females from conspecific females based on their cuticular hydrocarbon profiles (Peterson et al., )—chemicals that insects commonly used to identify potential mates and that can contribute to premating barriers between species (e.g. Havens & Etges, ; Maroja et al., ; Rundle & Dyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Selection on male CHCs is likely to have been particularly acute in the Hawaiian archipelago due to the evolutionary loss of a major channel of sexual communication in these crickets, the male calling and courtship songs. Given that CHCs serve the dual functions of desiccation resistance and mate choice and are thereby subject to both ecological divergence and divergence due to sexual selection, CHCs may be particularly important traits for the processes of reproductive isolation and speciation (Higgie et al, 2000;Blows, 2002;Chung et al, 2014;Maroja et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given their general importance in mate choice in crickets, we might also expect CHCs to play an important role in species recognition. There are a few studies implying that this may be the case in G. integer, G. lineaticeps, and Allonemobius species (Otte and Cade, 1976;Paul, 1976;Leonard and Hedrick, 2009), and differences in CHC profiles have been found among species of rapidly diverging Laupala (Mullen et al, 2007(Mullen et al, , 2008, however, other than Maroja et al (2014), no studies have explicitly tested this prediction. Here, we investigate the role of chemical cues in species recognition between a pair of European field crickets.…”
Section: Introductionmentioning
confidence: 92%
“…Species of true crickets, which have been intensively studied in the context of reproductive isolation (reviewed by Veen et al, 2013), are rarely reported to use chemoreception for species recognition (but see Maroja et al, 2014). Like all other insect species, the exoskeletons of crickets bear lipid molecules known as cuticular hydrocarbons (CHCs).…”
Section: Introductionmentioning
confidence: 99%